If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(x + 3) = (x + 1)(x + 7) + 10 Reorder the terms: (5 + x)(x + 3) = (x + 1)(x + 7) + 10 Reorder the terms: (5 + x)(3 + x) = (x + 1)(x + 7) + 10 Multiply (5 + x) * (3 + x) (5(3 + x) + x(3 + x)) = (x + 1)(x + 7) + 10 ((3 * 5 + x * 5) + x(3 + x)) = (x + 1)(x + 7) + 10 ((15 + 5x) + x(3 + x)) = (x + 1)(x + 7) + 10 (15 + 5x + (3 * x + x * x)) = (x + 1)(x + 7) + 10 (15 + 5x + (3x + x2)) = (x + 1)(x + 7) + 10 Combine like terms: 5x + 3x = 8x (15 + 8x + x2) = (x + 1)(x + 7) + 10 Reorder the terms: 15 + 8x + x2 = (1 + x)(x + 7) + 10 Reorder the terms: 15 + 8x + x2 = (1 + x)(7 + x) + 10 Multiply (1 + x) * (7 + x) 15 + 8x + x2 = (1(7 + x) + x(7 + x)) + 10 15 + 8x + x2 = ((7 * 1 + x * 1) + x(7 + x)) + 10 15 + 8x + x2 = ((7 + 1x) + x(7 + x)) + 10 15 + 8x + x2 = (7 + 1x + (7 * x + x * x)) + 10 15 + 8x + x2 = (7 + 1x + (7x + x2)) + 10 Combine like terms: 1x + 7x = 8x 15 + 8x + x2 = (7 + 8x + x2) + 10 Reorder the terms: 15 + 8x + x2 = 7 + 10 + 8x + x2 Combine like terms: 7 + 10 = 17 15 + 8x + x2 = 17 + 8x + x2 Add '-8x' to each side of the equation. 15 + 8x + -8x + x2 = 17 + 8x + -8x + x2 Combine like terms: 8x + -8x = 0 15 + 0 + x2 = 17 + 8x + -8x + x2 15 + x2 = 17 + 8x + -8x + x2 Combine like terms: 8x + -8x = 0 15 + x2 = 17 + 0 + x2 15 + x2 = 17 + x2 Add '-1x2' to each side of the equation. 15 + x2 + -1x2 = 17 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 15 + 0 = 17 + x2 + -1x2 15 = 17 + x2 + -1x2 Combine like terms: x2 + -1x2 = 0 15 = 17 + 0 15 = 17 Solving 15 = 17 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 3(8)-3x=18 | | 40+4j=2(-4-13j) | | 64=d/-8+69 | | 3x-25=x+35 | | 6n+8=5 | | xy-y=a+d | | 5x+15x-7=5(4x+4) | | (3x-2)(x+3)=-6x-4 | | (x+5)(x-5)=(x+1)(x+7)+10 | | 3(x-9)+8=62 | | 2x*7=10 | | (4a+5b)(8a-7b)= | | 260=-v+165 | | 73.543-23.683= | | (2x-1)/4=(x+5)/3 | | 2a+3=(1)/(2)(6+4a) | | 7X=7.5 | | 13x+1=13x+59 | | 5+2(y-7)=3(y+1)-2 | | 2n-7/3 | | 2(2-2)=4 | | 25000-20000-15000=x | | 64-v=231 | | 2x+x+8=6x-3x+8 | | x/6-5 | | 22=-x+215 | | 8P+2=-3P-15 | | 25000-x=20000+15000 | | 7x-5x-7x+1=6x-6x-7 | | 3(x+3)=7x+6-4x+3 | | ma-st=5m+2 | | 10x+30x-8=8(5x+7) |